ChemInform Abstract: CpRu‐Catalyzed Asymmetric Dehydrative Allylation. Issue 44 (14th October 2013) - Kitamura, Masato; Miyata, Kengo; Seki, Tomoaki; Vatmurge, Namdev; Tanaka, Shinji
Abstract Review: 51 refs.